Anorexigenic Effects of Miglitol in Concert with the Alterations of Gut Hormone Secretion and Gastric Emptying in Healthy Subjects - Kaku, H.; Tajiri, Y.; Yamada, K. (Hormone and Metabolic Research, 2012)
Although the α-glucosidase inhibitor miglitol (MG) has been reported to have anorexigenic effects, the mechanism remains to be elucidated. The objective of this study was to explore the effects of MG on appetite in relation to concomitant changes in postprandial gut hormone levels. This randomized open-label crossover study included 20 healthy volunteers. The effects of 50 mg MG on glucagon-like peptide-1 (GLP-1), peptide YY (PYY), and ghrelin levels were assessed in conjunction with a simultaneous determination of appetite scores using visual analogue scales (VAS) over 3 h after the ingestion of a 592 kcal test cookie. Additionally, the gastric emptying rate (GER) was measured using breath 13CO2 appearance in 10 subjects. 12 subjects were administered 50 mg MG thrice a day for 1 week, and alterations of the gut hormone levels and the VAS scores for appetite were evaluated. MG pre-administration resulted in a significant enhancement of GLP-1 and PYY responses induced by the cookie ingestion. Following MG administration, ghrelin level declined at 1 h, with a persistent suppression during the postprandial phase in contrast to the restoration to the basal level without MG. Furthermore, MG pre-administration suppressed appetite and maintained satiety evaluated using a VAS rating with concomitant inhibition of GER after cookie ingestion. One-week administration of MG did not influence either gut hormone levels before a meal or VAS rating during a whole day. These observations suggest that MG exerts an anorexigenic effects with concomitant alterations of gut hormone secretions and gastric emptying after meal ingestion.
Keywords: α-glucosidase inhibitor; appetite; ghrelin; glucagon-like peptide-1; peptide YY; visual analogue scales